1993
DOI: 10.1210/jc.76.2.318
|View full text |Cite
|
Sign up to set email alerts
|

A furan fatty acid and indoxyl sulfate are the putative inhibitors of thyroxine hepatocyte transport in uremia

Abstract: We studied the effects of 3-carboxy-4-methyl-5-propyl-2-furan-propanoic acid (CMPF), indoxyl sulfate, and hippuric acid on iodide production by rat hepatocytes in primary cultures. We questioned whether these substances could explain the alteration of serum thyroid hormone parameters observed in renal failure. Iodide production from [125I]T4 by rat hepatocytes was significantly inhibited in the presence of serum from uremic patients. Serum concentrations of CMPF, indoxyl sulfate, and hippuric acid were markedl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
39
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 0 publications
0
39
0
Order By: Relevance
“…Free fractions of T 4 by tracer equilibrium dialysis are normal (32,33) or increased in ESRD patients (34), T 4 -binding globulin (TBG) concentrations are normal (33)(34)(35)(36)(37)(38) or increased (32,39), and transthyretin concentrations are normal (34), while serum albumin levels may be reduced (32,34,35). Inhibitors of T 4 binding to serum carrier proteins in euthyroid uremic patients may include elevated serum levels of 3-carboxy-4-methyl-5-propyl-2-furanpropanoic acid (CMPF), indoxyl sulfate, and hippuric acid in uremic serum (17,40), as well as increased serum levels of interleukin-l|3 (IL-1/3), tumor necrosis factor (TNF-a), and their respective specific inhibitors (41). In nonuremic patients, elevated levels of oleic acid (42), interleukin-6 (IL-6) (43), and TNF-a (44) may reduce T 4 binding to serum carrier proteins, as may elevated bilirubin and nonesterified fatty acids in association with hypoalbuminemia in hepatic failure (45).…”
Section: B Tmentioning
confidence: 99%
See 1 more Smart Citation
“…Free fractions of T 4 by tracer equilibrium dialysis are normal (32,33) or increased in ESRD patients (34), T 4 -binding globulin (TBG) concentrations are normal (33)(34)(35)(36)(37)(38) or increased (32,39), and transthyretin concentrations are normal (34), while serum albumin levels may be reduced (32,34,35). Inhibitors of T 4 binding to serum carrier proteins in euthyroid uremic patients may include elevated serum levels of 3-carboxy-4-methyl-5-propyl-2-furanpropanoic acid (CMPF), indoxyl sulfate, and hippuric acid in uremic serum (17,40), as well as increased serum levels of interleukin-l|3 (IL-1/3), tumor necrosis factor (TNF-a), and their respective specific inhibitors (41). In nonuremic patients, elevated levels of oleic acid (42), interleukin-6 (IL-6) (43), and TNF-a (44) may reduce T 4 binding to serum carrier proteins, as may elevated bilirubin and nonesterified fatty acids in association with hypoalbuminemia in hepatic failure (45).…”
Section: B Tmentioning
confidence: 99%
“…In addition, exogenous inhibitors of T 4 binding to serum carrier proteins, such as furosemide, nonsteroidal antiinflammatory drugs, and heparin, may play a role (46). Sera from sick patients also inhibit in vitro T 4 binding to solid matrices in assays (47) In addition to inhibiting T 4 binding to serum carrier proteins, CMPF, hippuric acid, and indoxyl sulfate in uremic sera and bilirubin and nonesterified fatty acids in nonuremic sera inhibit T 4 uptake by rat hepatocytes in vitro (17,40,45,49). Circulating inhibitors from sera of other sick patients also interfere with uptake of T 4 by rat hepatocytes (47) and cultured human hepatoma cells (50).…”
Section: B Tmentioning
confidence: 99%
“…Because the plasma concentrations of indoxylsulfate in patients with CRF were considerably high (417 ± 217 µ M ) compared to those in normal subjects (16 ± 11 µ M ) [30] and highly variable (74–940 µ M ) [3,31,32], relatively high concentrations (500–800 µ M ) of uremic substances were applied in this study. 3-Indoxylsulfate inhibited the formation of resorufin and 6β-hydroxytestosterone in a noncompetitive manner (fig.…”
Section: Discussionmentioning
confidence: 99%
“…3-Indoxylsulfate may be taken up into the hepatocytes actively. Although the transport of thyroxine into hepatocytes has been shown to be inhibited by indoxylsulfate [30], there has been no reported study supporting the active transport of indoxylsulfate into hepatocytes. Although the plasma concentration of indoxylsulfate is highly variable, the results of microsome and hepatocytes suggest that relatively high concentration of indoxylsulfate in the liver is required to cause clinically significant inhibition of metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, 3-carboxy-4-methyl-5-propyl-2-furanpropanoic acid (CMPF) (Scheme 1) in an endogenous, ligand is tightly bound to serum protein (17,18) and, there-fore, the concentration of CMPF in uremic plasma is not significantly decreased by hemodialysis (19). Recently, it was suggested that CMPF inhibits transport of thyroxine into hepatocytes in uremia (20), inhibits the active uptake of thyroxine into anterior pituitary cells (21), and enhances drug inhibition of thyroxine binding in serum (22). Analysis of CMPF has previously been performed by gas chromatographic (23), and gas chromatographic-mass spectrometric techniques (24), as well as by high-performance liquid chromatography (19) but these methods require sample preparation and can be inconvenient for routine screening of many samples.…”
mentioning
confidence: 99%